Historiographic Analysis of the Role of Christian Culture in the Formation of the Yakut Writing System - Rufova, Elena Stepanovna; Sivtceva-Maksimova, Praskovia Vasilievna (Journal of History Culture and Art Research, 2020)
This manuscript studies the role of Christian culture and missionary efforts in the process of the interpenetration of Russian and Yakut cultures. In the pre-revolutionary period, conversion to Christianity played an important role as a unifying factor in relations between peoples and in the formation of self-consciousness of the Sakha people as an integral part of the multinational Russian people. A special study of the significance of Christian culture in the development of the literature of the Sakha people represents a new scientific direction in the study of the history of Yakut literature. In this perspective, special attention is paid to the study of early editions of spiritual literature in the source study aspect. The relevance of the manuscript is in the study of early sources stored in museums and archives of the republic and beyond. The study systematizes the historical sources and literature on the efforts of Saint Innocent of Alaska, who played a significant role in the development of not only the Yakut Diocese but also in the development of the spiritual culture of the Yakuts. The personal contribution of Saint Innocent of Alaska is highlighted, during whose missionary efforts significant historical events occurred in Yakutia - the first translated publications and the conduct of church services to the Yakut language.